The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/plants11202785
|View full text |Cite
|
Sign up to set email alerts
|

Organic Mulches as an Alternative to Conventional Under-Vine Weed Management in Mediterranean Irrigated Vineyards

Abstract: Vineyard growth and grape yield can be significantly reduced by weeds, especially when these are located in the under-vine zone. Traditional weed management consists of recurrent tillage, which is associated with soil erosion and high fuel consumption, or herbicide applications, associated with damage to the environment and human health. In order to find alternative weed management methods, three field trials were carried out in Raimat (Lleida, NE Spain) with the aim of evaluating the suppressive effect of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Its effectiveness to maintain low levels of weed coverage and frequency has already been reported byValencia-Gredilla et al (2020) andCabrera- Pérez (2022). In the present study, all annual cover crops were shredded in June, at the end of their life cycle.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Its effectiveness to maintain low levels of weed coverage and frequency has already been reported byValencia-Gredilla et al (2020) andCabrera- Pérez (2022). In the present study, all annual cover crops were shredded in June, at the end of their life cycle.…”
supporting
confidence: 77%
“…Hordeum vulgare , offered an efficient control of C. dactylon , with low weed cover values across the three seasons (Table 1). Its effectiveness to maintain low levels of weed coverage and frequency has already been reported by Valencia‐Gredilla et al (2020) and Cabrera‐Pérez (2022). In the present study, all annual cover crops were shredded in June, at the end of their life cycle.…”
Section: Discussionmentioning
confidence: 60%
“…Mulch is any bulk material placed on the soil surface to control weeds and/or preserve moisture. Environmentally-friendly organic mulches suppress weed emergence by creating a physical barrier intercepting light/temperature and through the release of allelochemicals inhibiting weed seed germination (Cabrera-Pérez et al, 2022). Recent studies showed that lignin-rich materials such as chopped pine wood, pruning waste, almond shell etc.…”
Section: Dead and Organic Mulchesmentioning
confidence: 99%
“…Recent studies showed that lignin-rich materials such as chopped pine wood, pruning waste, almond shell etc. decompose slowly facilitating long-term suppression of intra-row weeds in orchards/vineyards (Cabrera-Pérez et al, 2022;Goh & Tutua, 2004;L opez-Urrea et al, 2020). For physical weed control in tree crops, there is also potential to develop precision agricultural machinery.…”
Section: Dead and Organic Mulchesmentioning
confidence: 99%
“…These should include a mixture of different modes of action (MoA), mechanical control (mowing and shredding), or cover crops among others. Finally, organic mulches under crop plants or bioherbicides are promising new tools to consider for managing Conyza [ 18 , 19 ].…”
Section: Herbicide-resistant Cases In Perennial Cropsmentioning
confidence: 99%